Pengaruh Sales Growth, Leverage, dan Efisiensi Operasional terhadap Kinerja Keuangan Perusahaan Transportasi dan Logistik - Salma Nur Zahirah; Fanji Farman (Owner : Riset dan Jurnal Akuntansi, 2026)
Mobility, national distribution, and overall economic activity are supported by the transportation and logistics industry, which plays a strategic role. However, companies in this industry may see their net profits impacted by inflationary pressures, supply chain disruptions, and rising operating costs. The objective of this study is to examine the financial performance of logistics and transportation companies listed on the IDX from 2021 to 2024, focusing on the impact of sales growth, leverage, and operational efficiency. Using secondary data collected from the annual reports of the sample companies, this study employs a quantitative method. Using a purposive sampling approach, the sample was determined to consist of a total of 28 companies and 112 observations. Several observations were identified as outliers during data processing, reducing the sample size to 84 observations. The researcher used EViews 13 panel data regression to analyze the data. This study used REM as the basis for model selection. The results indicate that companies’ financial performance is significantly influenced by the simultaneous effects of sales growth, leverage, and operational efficiency. Unlike sales growth and leverage, operational efficiency improves financial performance. Based on these results, it appears that companies can increase net profit by managing operational efficiency more effectively. By providing up-to-date actual data, this study contributes to the existing literature and emphasizes the importance of operational efficiency in determining financial success in the logistics and transportation industry.